(untitled) (Economic and Political Thought, 2018)
The article focuses on the process of developing a new Eurasian order and Russia and China’s contemporary imperial projects in the region. The author asks a few important questions concerning the foundations of both states’ perception of Eurasian strategies as well as the level of complementarity and competitiveness of those projects organising the Eurasian space in the Sino-centric or Russo-centric perspective. The main thesis contains an opinion that Russian-Chinese relations at a given stage and in the foreseeable future will tend to harmonisation and relative complementarity, which is also observed in an attempt to synchronise the Eurasian Economic Union with the Chinese idea of reviving the Silk Road joining Europe with Asia. Neither Moscow nor Beijing will expose the conflict of interests and rivalry so characteristic of superpowers. The situation results from the fact that both states have a very good understanding that strategic rivalry at a given stage of development of their bilateral relations is not advantageous for any of them. This similar perception of the international situation and the will to limit, and perhaps in further future eliminate, the USA’s dominance in Eurasia make an adhesive of Russia and China’s strategic partnership. Chinese and Russian authorities are aware of the advantage they have in imperial efforts thanks to complementarity of potentials and coordination of joint as well as individual activities on the international arena.